Overview of the observations of the MVP-MTZ in the southern part of the Kirovograd anomaly of electrical conductivity and the first experience of film modeling of the structure of the Ukrainian Shield - I. I. Rokityansky; A. V. Teryoshin; V. I. Tregubenko; N. S. Golubtsova; A. I. Ingerov; T. S. Savchenko (Геофизический журнал, 2012)
Brief review of the earlier studies of Kirovograd electrical conductivity anomaly with emphasis on the field data is presented. The influence of S-effect on the magnetotelluric sounding (MTS) curves in the Ukrainian Shield was estimated by thin film modeling. Comparison of the modeling results with MTS field data shows that resistivity of upper part of consolidated crust underlying sediments in the Ukrainian Shield is regionally much lower than expected. Our recent field data have been presented showing that the Kirovograd electrical conductivity anomaly continues under the Black Sea.